2022
DOI: 10.3390/app122110761
|View full text |Cite
|
Sign up to set email alerts
|

Malicious File Detection Method Using Machine Learning and Interworking with MITRE ATT&CK Framework

Abstract: With advances in cyber threats and increased intelligence, incidents continue to occur related to new ways of using new technologies. In addition, as intelligent and advanced cyberattack technologies gradually increase, the limit of inefficient malicious code detection and analysis has been reached, and inaccurate detection rates for unknown malicious codes are increasing. Thus, this study used a machine learning algorithm to achieve a malicious file detection accuracy of more than 99%, along with a method for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Risks other than these, i.e., "unknown-unknowns", are excluded. The risks associated with this type of risk need to be considered based on concepts such as offensive security [17] and MITER ATT&CK [18], and remain a topic for future work.…”
Section: Limitations Of This Papermentioning
confidence: 99%
“…Risks other than these, i.e., "unknown-unknowns", are excluded. The risks associated with this type of risk need to be considered based on concepts such as offensive security [17] and MITER ATT&CK [18], and remain a topic for future work.…”
Section: Limitations Of This Papermentioning
confidence: 99%
“…The main aim of this study from [Ahn et al 2022] was to perform a dynamic analysis of malicious and suspicious files and apply the results to the MITRE ATT&CK framework to visually present the attack tactics and detailed techniques used for the files. The proposal was to make it easier for agents to identify and respond to threats.…”
Section: Related Workmentioning
confidence: 99%
“…Most research found in the state of the art has the objective of detecting and recognizing patterns in combating malicious adversaries [Ahn et al 2022, Lin et al 2022, Noor et al 2019]. However, these works have addressed this problem through proposals for a cyber threat attribution using unstructured reports in cyber threat intelligence [Irshad and Siddiqui 2022] and an automated reclassification for threat actors [Shin et al 2021].…”
Section: Introductionmentioning
confidence: 99%
“…The study [11] using same dataset combined a method for visualising data for the detection of malicious les utilizing the dynamic-analysis-based MITRE ATT&CK framework with a machine learning algorithm to obtain a harmful le detection accuracy of more than 99%. Three models were used to categorise the PE malware dataset: Random Forest, Adaboost, and Gradient Boosting.…”
Section: Experimental Analysismentioning
confidence: 99%